Multiple circle-shaped lesions on two individuals from the preroman necropolis of Bazzano (Aq - Central Italy) (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: cranial lesion; trauma; Abruzzo